2014
DOI: 10.3390/rs6098337
|View full text |Cite
|
Sign up to set email alerts
|

NDVI-Based Long-Term Vegetation Dynamics and Its Response to Climatic Change in the Mongolian Plateau

Abstract: Abstract:The response of vegetation to regional climate change was quantified between 1982 and 2010 in the Mongolian plateau by integrating the Advanced Very High Resolution Radiometer (AVHRR) Global Inventory Modeling and Mapping Studies (GIMMS) normalized difference vegetation index (NDVI) and the Moderate Resolution Imaging Spectroradiometer (MODIS) NDVI (2000NDVI ( -2010. Average NDVI values for the growing season (April-October) were extracted from the AVHRR and MODIS NDVI datasets after cross-calibratin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
98
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 161 publications
(133 citation statements)
references
References 50 publications
9
98
0
Order By: Relevance
“…16.64% of areas have undergone slowed down NDVI trends, especially in northern grassland, which could be partly contributed by the slowed down trends of temperature in these areas since mid 1990s (Figure 10c,d). The study by Bao et al [20] also indicated the decreasing trends of NDVI in the Mongolian Plateau since mid or late 1990s. In some arid and semi-arid areas such as southern Tibetan and northern Xinjiang, speeded up temperature increment could limit the water availability for vegetation hence led to stalled NDVI trends [55].…”
Section: Abrupt Change In Ndvi and Its Relationship To Climatic Driversmentioning
confidence: 92%
See 2 more Smart Citations
“…16.64% of areas have undergone slowed down NDVI trends, especially in northern grassland, which could be partly contributed by the slowed down trends of temperature in these areas since mid 1990s (Figure 10c,d). The study by Bao et al [20] also indicated the decreasing trends of NDVI in the Mongolian Plateau since mid or late 1990s. In some arid and semi-arid areas such as southern Tibetan and northern Xinjiang, speeded up temperature increment could limit the water availability for vegetation hence led to stalled NDVI trends [55].…”
Section: Abrupt Change In Ndvi and Its Relationship To Climatic Driversmentioning
confidence: 92%
“…The influence of climate on vegetation dynamics has drawn increasing attention in the past few decades [14][15][16][17][18][19][20]. Long-term remote sensing observations provide effective methods to investigate interannual vegetation dynamics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multispectral band combinations of these datasets have aided the retrieval of long time series of land surface variables widely used to examine trends in vegetation dynamics at global, regional and national scales (Bao et al, 2014;Julien and Sobrino, 2009), impacts of vegetation on water and energy flux (Hu 10 et al, 2009) as well as the correlation between vegetation and climate conditions (Bao et al, 2014). Particularly, Leaf Area Index (LAI), which is defined, in broadleaf canopies, as the one-sided green leaf area per unit vegetated ground area, and in coniferous canopies, as one-half the total needle surface area per unit vegetated ground area.…”
Section: Introductionmentioning
confidence: 99%
“…Terrestrial vegetation depend on and affect land surface-atmosphere interactions as the primary link for moisture 25 (evapotranspiration) and energy (latent) exchange through its physiological properties (Leaf Area Index-LAI, rooting depth and stomatal resistance), and its influence on surface roughness, and albedo (Arora, 2002;Bao et al, 2014;Ning et al, 2015). For instance, recent studies have reported a strong land-atmosphere coupling in West Africa, whereby vegetation dynamics play a significant role in regulating the West Africa monsoon and therefore rainfall distribution (Hales et al, 2006;Xue et al, 2012;Zheng and Eltahir, 1998).…”
Section: Introductionmentioning
confidence: 99%